Perlindungan Hukum terhadap Korban Kekerasan dalam Rumah Tangga yang Dilakukan oleh Pelaku Pengguna Napza - Rida Putri Subrata; Ismayana; Siska Karina (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study aims to analyze legal protection for victims of domestic violence committed by perpetrators who use drugs and the obstacles in its implementation. The study uses an empirical juridical method with a statutory regulatory approach and field research through interviews and literature studies. The results of the study indicate that legal protection has been regulated in Law Number 23 of 2004 concerning the Elimination of Domestic Violence and Law Number 3 of 2026 concerning the Protection of Witnesses and Victims and is supported by assistance services by the DP3APPKB of Cirebon City. However, its implementation is not optimal because victims tend not to report due to fear, lack of understanding of legal procedures, economic dependence on the perpetrator and the perpetrator's characteristics as a drug user. Therefore, it is necessary to strengthen legal education, coordination between agencies and protection services that are more easily accessible to victims.